2021
DOI: 10.1093/infdis/jiab324
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Identification of T-Cell Epitopes Derived From Severe Acute Respiratory Syndrome Coronavirus 2 for the Development of Peptide Vaccines Against Coronavirus Disease 2019

Abstract: Background Coronavirus disease-19 (COVID-19) continues to be a major public health challenge globally. The identification of SARS-CoV-2-derived T cell epitopes is of critical importance for peptide vaccines or diagnostic tools of COVID-19. Methods In this study, a number of SARS-CoV-2-derived HLA-I binding peptides were predicted by NetMHCpan-4.1 and selected by Popcover to achieve pancoverage of the Chinese population. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…SARS-CoV-2 specific T cells targeting a highly conserved epitope derived from the RdRp protein (RdRp 829-838, LPYPDPSRIL) were identified from several healthy donors in our previous study, and this epitope was predicted to be HLA-B*51:01 restricted by NetMHCpan4.1 [17] , [20] . CD8 + 4-1BB + T cells were sorted from one pre-pandemic healthy donor for expansion followed by activity verification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2 specific T cells targeting a highly conserved epitope derived from the RdRp protein (RdRp 829-838, LPYPDPSRIL) were identified from several healthy donors in our previous study, and this epitope was predicted to be HLA-B*51:01 restricted by NetMHCpan4.1 [17] , [20] . CD8 + 4-1BB + T cells were sorted from one pre-pandemic healthy donor for expansion followed by activity verification.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-existing T cells targeting a highly conserved epitope from RdRp protein have been identified in previous study [17] . The epitope-specific T cells were then sorted and expanded as follows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained by using these methods suggested that generation of effective adaptive immunity against SARS-CoV-2 requires the participation of both CD4+ and CD8+ T cells. This finding is very important for the preparation of a functional vaccine, as it is clear that it is necessary to incorporate both HLA-I-restricted and HLA-II-restricted epitopes in peptide-based vaccines to obtain optimal vaccination [53].…”
Section: Peptides Used For Identification Of Sars-cov-2-derived T Cell Epitopesmentioning
confidence: 99%
“…Among the variants of SARS-CoV-2, the Delta variant (B.1.617.2) has dominated over other variants during the intense COVID-19 wave in India in April-May 2021, due to its higher transmissibility and partial evasion of the host immune responses 15 . Previous studies have suggested the possibility of T cell immune escape in SARS-CoV-2 variants 16,17,19 as well as isolates of the Wuhan strain 18 either restricted to certain HLA alleles 16,17,19 or covering larger populations 18,20 . On the contrary, mutations arising in the emerging variants have been reported to facilitate escape, mainly from the neutralizing antibody response rather than the T cell responses which are relatively more conserved across variants 21,22 .…”
Section: Introductionmentioning
confidence: 99%